Analisis Strategi Komunikasi Pemasaran Dan Strategi Promosi Vivo Smartphone Dalam Meningkatkan Brand Awareness Di Kalangan Remaja Kelurahan Kedaleman Kecamatan Cibeber Cilegon Banten - Novita Nisfu Ramadhona; Hastono Hastono (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the marketing communication strategy and promotional strategy of Vivo Smartphone in increasing brand awareness among teenagers. The rapid growth of the smartphone industry has created intense competition among companies in attracting consumers, particularly in the teenage segment, which represents a highly potential market with unique characteristics such as high technology usage, strong engagement with social media, and a tendency to follow trends. This situation requires companies to develop effective communication and promotional strategies to attract attention and build emotional connections with young consumers.This research employs a descriptive qualitative approach with data collection techniques including in-depth interviews with teenage Vivo users and smartphone sellers, direct observation of promotional activities, and documentation of digital campaign materials. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, referring to the Miles and Huberman model, with data validity strengthened through source and method triangulation.The results of the study indicate that Vivo consistently utilizes digital media as the main tool for marketing communication, aligning with the lifestyle of teenagers. The strategies implemented include the use of social media, creative digital campaigns, collaborations with influencers, and interactive advertisements to build emotional engagement. In addition, promotional strategies are carried out through event sponsorships, collaborations with e-commerce platforms, discount programs, and product bundling. The combination of integrated communication strategies and innovative promotions has proven effective in enhancing consumer interaction, expanding market reach, and strengthening Vivo’s brand awareness and competitiveness among teenagers